Objective response by mRECIST to initial lenvatinib therapy is an independent factor contributing to deep response in hepatocellular carcinoma treated with lenvatinib-transcatheter arterial chemoembolization sequential therapy - Hidekatsu Kuroda; Takayoshi Oikawa; Masashi Ninomiya; Masashi Fujita; Kazumichi Abe; Kazuo Okumoto; Tomohiro Katsumi; Wataru Sato; Go Igarashi; Chikara Iino; Tetsu Endo; Nobukazu Tanabe; et al. (Liver Cancer, 2022)
Objective: There is limited information regarding the benefits of Lenvatinib-transcatheter arterial chemoembolization (LEN-TACE) sequential therapy for unresectable hepatocellular carcinoma (u-HCC). We compared the efficacy and safety of LEN-TACE sequential therapy to LEN monotherapy and investigated the factors contributing to the LEN-TACE sequential therapy deep response. Methods: We enrolled a multi-center cohort of 247 patients with u-HCC treated with LEN between 2018 and 2020. Propensity score matching identified sixty-three matching pairs of patients with well-balanced characteristics. We retrospectively compared the clinical outcomes, including overall survival (OS), progression-free survival (PFS), and incidence of adverse events (AEs), between the LEN-TACE and LEN monotherapy groups. Additionally, we evaluated the tumor response, change in albumin-bilirubin (ALBI) score, factors affecting PFS and OS, and independent predictors contributing to the LEN-TACE sequential therapy deep response. In this study, at eight weeks after resumption of LEN after initial TACE, "deep response" was defined as achieving CR or PR on mRECIST, and at least a 30% decrease in the sum of diameters of target lesions, taking the baseline sum diameters as the reference. Results: The OS and PFS in the LEN-TACE group were significantly higher than those in the LEN monotherapy group (P = 0.002 and P = 0.037, respectively). The incidence of AEs related to LEN was not significantly different between the two groups. In LEN-TACE sequential therapy, the objective response rate was 61.9%, and the disease control rate was 74.6%, according to the mRECIST criteria. No significant change in the ALBI score was observed during sequential LEN-TACE therapy. Multivariable analyses revealed that deep response was independently associated with the outcome of the initial response to LEN by mRECIST: PR (odds ratio: 13.75, 95% CI: 0.41–1.32, P <0.001). Conclusions: LEN-TACE sequential therapy may provide more clinical benefits than LEN monotherapy in u-HCC patients who responded to initial LEN treatment. Objective response according to mRECIST to initial LEN is an independent factor contributing to LEN-TACE sequential therapy deep response.